Developing an online project-based assessment instrument for assessing students’ historical thinking skills - Ofianto, Ofianto; Saputra, Nanda; Ningsih, Tri Zahra; Nababan, Surya Aymanda; Asri, Zul; Aman, Aman; Setiawan, Johan (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to provide a comprehensive evaluation of historical thinking that can be applied to all aspects of online historical thinking skills. The analysis proposed by Gall was used in developing the model and it involves the following stages: instrument design; instrument development; analysis; and initial data collection. A total of 148 high school students participated in this study, and data were gathered through literature analysis sheets, interviews, needs analysis questionnaire for the development of e-project skills assessment tools, expert validation test, and e-project assessment. The findings showed that the e-project is valid and reliable for evaluating historical thinking skills in remote learning, with all components having a high reliability rating of 0.78 and validity values ranging from 0.77 to 1.30. Subsequently, a valid, reliable, and acceptable e-project website was created to assess student’s competence in historical thinking. This research offers options for teachers to effectively assess and monitor students’ historical thinking skills while also improving a more interactive and interesting learning style.